Incidence of Circulating Antibodies Against Hemagglutinin of Influenza Viruses in Epidemic Season 2023/2024 in Poland - Katarzyna Kondratiuk; Aleksander Masny; Anna Poznańska; Karol Szymański; Katarzyna Łuniewska; Emilia Czajkowska; Bartosz Mańkowski; Lidia B. Brydak (Biomolecules, 2025)
The aim of this study was to determine the level of anti-hemagglutinin antibodies using the hemagglutination inhibition test (HAI) in the blood sera of patients collected during the 2023/2024 epidemic season in Poland. This data is valuable for assessing the level of population immunity to influenza viruses circulating in Poland during this epidemic season. The study material consisted of serum samples collected across the country and divided into seven age groups. The test results confirmed the presence of anti-hemagglutinin antibodies for the antigens included in the quadrivalent influenza vaccine recommended by the World Health Organization (WHO) for the 2023/2024 epidemic season: A/Victoria/4897/2022 (H1N1)pdm09, A/Darwin/9/2021 (H3N2), B/Austria/1359417/2021 (B/Victoria lineage) and B/Phuket/3073/2013 (B/Yamagata lineage). The highest values of the geometric mean (GMT = 121.0 [95% CI: 108.5–134.9]) and protective factor (70 [95% CI: 67–74]%) were recorded for the A/H3N2/influenza virus antigen. In Poland, the vaccination rate of the general population in the discussed season was only 5.52%. The obtained results can therefore be interpreted as a response of the immune system, consisting of the production of anti-hemagglutinin antibodies in patients who had previously had an infection caused by the influenza virus.